Conflict resolution and the scholarship of engagement: partnership transforming conflict / edited by Cheryl Lynn Duckworth and Consuelo Doria Kelley - Duckworth, Cheryl Lynn (ed.); Kelley , Consuelo Doria (ed.) (New Castle, 2012)
As the field of conflict analysis and resolution continues to grow, scholars and practitioners increasingly recognize that we can learn from one another. Theory must be informed by practice and practice must draw on sound theory. Above and beyond this lies a further recognition: without at least attempting to actually engage and transform entrenched conflicts, our field cannot hope to achieve its potential. We will merely remain in a more diverse, multi-disciplinary ivory tower. This edition breaks new ground in explicitly connecting the Scholarship of Engagement to the work of conflict resolution professionals including those in the academy, those in the field, and those who refuse to choose between the two. The text explores a wide variety of examples of, and thinking on, the Scholarship of Engagement from participatory action research to peace education, and from genocide prevention to community mediation and transitional justice.
Keywords: Conflict management